Improvement on mitochondrial energy metabolism of Codonopsis pilosula (Franch.) Nannf. polysaccharide - Li, He; Zhang, Letian; Li, Xingtai; He, Haocheng; Fu, Guoan; Zhu, Yi Zhun; Hu, Wei; Qiu, Lige; Gong, Liang; Zhang, Youming (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceCodonopsis pilosula (Franch.) Nannf. (CP) is one of the most popular Qi-invigorating herbal medicines and has been extensively used to promote health and vitality in China for a long time. Codonopsis pilosula (Franch.) Nannf. polysaccharide (CPP) is the principal active components of CP, which is considered as the reason for CP widespread application. However, it has not been revealed that CPP exert a Qi-invigoration effect by protecting mitochondria and/or improving mitochondrial function in the existing traditional Chinese medicine theories.Aim of the studyWe extracted CPP from C. pilosula and investigated the effects of CPP on energy metabolism and mitochondrial protection.MethodsBased on the mice chronic hypoxia model for imitating the energy deficiency state of the human body, which was administered with CPP by oral gavage daily for 10 days, mitochondrial permeability transition (MPT), lipid peroxidation product malondialdehyde (MDA) in brain, mitochondrial respiratory function, the levels of adenosine triphosphate (ATP), adenosine diphosphate (ADP) and adenosine monophosphate (AMP) in liver cells were assayed. Adenylate energy charge (AEC), total adenylate pool (TAP), ATP/ADP, and ATP/AMP ratios were calculated.ResultsCPP can inhibit the formation of MDA in mice brains, decrease oxygen consuming rate and respiratory control ratio (RCR) of liver mitochondria, increase levels of ATP, TAP and AEC in liver cells under chronic hypoxia condition.ConclusionCPP can possess and improve mitochondrial energy metabolism and bioenergetic levels.